Relationship between menstrual cycle and recurrent aphthous stomatitis - Arma, Utmi; Bakar, Abu; Yosmiryanti, Melin (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Recurrent Aphthous Stomatitis (RAS), also known as apthae or canker sores is an ulcerated lesion that occurs repeatedly on the oral mucosa. The etiology of RAS is not yet known for certain, but there are predisposing factors associated with the occurrence RAS, one of them is the menstrual cycle. The menstrual cycle is a sign of the maturation process of the reproductive organs which is influenced by the body's hormones. The menstrual cycle occurs in 4 phases, namely the menstrual phase, the follicular phase, the ovulation phase, and the luteal phase. The purpose of this study was to determine the relationship between the menstrual cycle and RAS. Methods: The type of this research is an analytic observational study using a cross-sectional design, the research was conducted in Kampung Jawa, Solok City, West Sumatra from September 2021 to March 2022 with 94 respondents who were taken by accidental sampling. Data collection was carried out by giving questionnaires/google forms to women aged 15-24 years to obtain data related to menstrual cycle and RAS. Data analysis was performed by Chi-Square test. Results: Most of the respondents are negative respondents to experiencing RAS during their menstrual cycle amounting to 54 respondents (57.4%), and followed by positive respondents experiencing RAS in the menstrual cycle amounting to 40 respondents (42.6%). The test results show a significant relationship between the menstrual cycle and RAS (p = 0.153). Conclusion: There is no relationship between the menstrual cycle and the occurrence of RAS. There are more respondents who negatively experience RAS in the menstrual cycle than positive respondents experiencing RAS in their menstrual cycle.KEY WORDS: Cycle, menstruation, aphthous stomatitis, recurrent, womenHubungan siklus menstruasi dengan stomatitis aftosa rekurenABSTRAKPendahuluan: Stomatitis Aftosa Rekuren yang dikenal dengan istilah apthae atau canker sore merupakan suatu lesi ulserasi yang terjadi berulang pada mukosa mulut. Etiologi SAR sampai saat ini belum diketahui secara pasti, namun ada faktor predisposisi yang berhubungan dengan terjadinya SAR, salah satunya adalah siklus menstruasi. Siklus menstruasi adalah tanda proses kematangan organ reproduksi yang dipengaruhi oleh hormon tubuh. Siklus menstruasi terjadi dalam 4 fase yaitu fase menstruasi, fase folikuler, fase ovulasi, dan fase luteal. Tujuan penelitian ini menganalisis hubungan siklus menstruasi dengan SAR. Metode: Jenis penelitian observasional analitik menggunakan desain cross sectional, penelitian dilakukan di Kampung Jawa, Kota Solok, Sumatra Barat pada bulan September 2021 hingga Maret 2022 dengan 94 responden yang diambil secara accidental sampling. Pengambilan data dilakukan dengan memberikan kuesioner/google form kepada perempuan berumur 15-24 tahun. Analisis data dilakukan dengan uji Chi-Square. Hasil: Sebagian besar responden negatif mengalami SAR pada siklus menstruasi yaitu sebanyak 54 responden (57,4%) dan diikuti responden yang positif mengalami SAR pada siklus menstruasi sebanyak 40 responden (42,6%).Hasil uji menunjukan hubungan bermakna antara siklus menstruasi dengan SAR (p=0,153). Simpulan: Tidak terdapat hubungan antara siklus menstruasi dengan terjadinya SAR. Terdapat lebih banyak responden yang negatif mengalami SAR pada siklus menstruasi dibandingkan responden yang positif mengalami SAR pada siklus menstruasi.KATA KUNCI: Siklus, menstruasi, stomatitis aftosa, rekuren, wanita